2017
DOI: 10.20414/iqtishaduna.v8i1.356
|View full text |Cite
|
Sign up to set email alerts
|

Transmisi Kebijakan Moneter Jalur Pembiayaan Bank Syariah Di Indonesia

Abstract: This research aims to examine the role of Sharia Banks on the financingchannel monetary transmission mechanism in Indonesia. Using data fromJanuary 2014 – December 2016, this study applies Vector Error CorrectionModel (VECM). Variables that represent sharia banking are third partyfund (DPK) dan financing (FIN). Variable that represents monetary policyis rate of Central Bank Sharia Certificate (SBIS) and monthly economicgrowth proxied by Industrial production Index (IPI). This research showsthat monetary policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…These results show that, in general, shocks to the OMO variable respond negatively to IPI. This is consistent with the findings of Imaduddin (2019), Syapriatama (2017), and Wibowo and Mubarok (2018). Islamic banking is more interested in placing its funds in Bank Indonesia if the SBIS tends to be high, so there is no need to channel funds through financing to customers (Rusydiana, 2009).…”
Section: Figure 3 Irf Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results show that, in general, shocks to the OMO variable respond negatively to IPI. This is consistent with the findings of Imaduddin (2019), Syapriatama (2017), and Wibowo and Mubarok (2018). Islamic banking is more interested in placing its funds in Bank Indonesia if the SBIS tends to be high, so there is no need to channel funds through financing to customers (Rusydiana, 2009).…”
Section: Figure 3 Irf Resultssupporting
confidence: 93%
“…Indicators can be used to see economic growth or output, namely the growth of Gross Domestic Product (GDP) (Wibowo & Mubarak, 2017). Monthly economic growth can be observed through the Industrial Production Index (IPI) indicator (Syapriatama, 2017). The sluggish economic activity in Indonesia impacts not only the growth rate of gross domestic products, but also the manufacturing and industrial sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Even Asnuri from his research found that SBIS has a negative effect on economic growth in the short and long term (Asnuri, 2015). This result was also shown by Syapriatama's research in which SBIS responded negatively to the economy (Syapriatama, 2017).…”
Section: Discussionmentioning
confidence: 75%
“…Likewise, Asnuri (2015) revealed that SBIS had a significant negative impact on short and long-term economic growth. Syapriatama (2017) stated that Islamic monetary policy and Islamic banks have a significant impact on economic growth. He used SBIS to represent Sharia monetary policy, and he believed that the bonus level of this SBIS indicated a shift toward Bank Indonesia policy, either loose or tight.…”
Section: Introductionmentioning
confidence: 99%